2013
DOI: 10.1093/toxsci/kft244
|View full text |Cite
|
Sign up to set email alerts
|

Test of the Usefulness of a Paradigm to Identify Potential Cardiovascular Liabilities of Four Test Articles With Varying Pharmacological Properties in Anesthetized Guinea Pigs

Abstract: The evaluation of proarrhythmic and hemodynamic liabilities for new compounds remains a major concern of preclinical safety assessment paradigms. Contrastingly, albeit functional liabilities can also translate to clinical morbidity and mortality, lesser preclinical efforts are focused on the evaluation of drug-induced changes in inotrope and lusitrope, particularly in the setting of concomitant hemodynamic/arrhythmic liabilities. This study aimed to establish the feasibility of an anesthetized guinea pig prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…negative lusitrope) may result from β-blocking effect of dronedarone which prevents phosphorylation of phospholamban; therefore, less calcium is resequestrated through the SERCa 2+ channel resulted in slow relaxation [4]. This result is also in accordance with our previous study in which dP/dt min and tau were lengthened when metoprolol was given to anesthetized guinea pigs [17]. The end-diastolic pressure-volume relationship (EDPVR) has been used as an index of lusitrope, since it measures the relationship between pressure and volume at the end-diastole [5].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…negative lusitrope) may result from β-blocking effect of dronedarone which prevents phosphorylation of phospholamban; therefore, less calcium is resequestrated through the SERCa 2+ channel resulted in slow relaxation [4]. This result is also in accordance with our previous study in which dP/dt min and tau were lengthened when metoprolol was given to anesthetized guinea pigs [17]. The end-diastolic pressure-volume relationship (EDPVR) has been used as an index of lusitrope, since it measures the relationship between pressure and volume at the end-diastole [5].…”
Section: Discussionsupporting
confidence: 89%
“…Similar to the results of tau and dP/dt min , EDPVR was elevated at an escalating dose of 2.5 mg/kg compared to baseline, suggesting diastolic dysfunction due to acute effect of β-blockade. The similar result was observed when escalating doses of metoprolol were given intravenously in anesthetized guinea pigs [17]. …”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Recent studies in anesthetized guinea pigs and dogs demonstrated that contractility index is more reliable for assessment of inotropic state of the heart than dP/dt max (Kijtawornrat et al, 2014). The relaxation of the right and left ventricle of rabbit with RVH also decreased significantly as assessed by tau (for only the left ventricle).…”
Section: Functional Remodeling Of the Ventriclementioning
confidence: 99%
“…Ultimately however, an in vivo risk assessment is required to build on in vitro data (Hamlin & Del Rio, 2010). While the measurement of left ventricular pressure in small and/or large animal models can be used as an index of effects on drug-induced contractility (Hamlin & del Rio, 2012;Kijtawornrat et al, 2014), for compounds with a significant effect, translatable data such as ejection fraction obtained via echocardiography in repeat-dose toxicology studies represent the final step for an integrated risk assessment (Redfern et al, 2013). These types of data were illustrated with examples from in-house discovery projects.…”
Section: Preclinical Detection Of Inotropic Effects Of Drugs Dr Chrismentioning
confidence: 99%